STRATEGY WATER-BASED CONDENSER : An Experimental Scale Model for Hybrid Passive Cooling Systems to Improve Indoor Temperature and Hot Water Utilities in Surabaya-Indonesia (DIMENSI: Journal of Architecture and Built Environment, 2005)
This paper makes a case of energy saving research, to system water-based condenser for the use of energy efficient with involvement of forced fluid hybrid passive cooling and water heating in building systems. Our argument is based on the fact that series of water copper pipes are to be cooled enough by nocturnal radiant cooling of the night cool air to lower the indoor air temperature at the daytime. We describe the model of working to which we use and to which we believe that series of cool water copper pipes as evaporator allows effectively reducing the energy used for indoor cooling and for water heating utilization. We then measure the model indoor temperature, and water temperature inside the series of copper pipes. Kinds of water coolant used for cooling are an essential factor. Finally, we will discuss some of the achieving of the effective cooled water, setting up the pipes water-based condenser hybrid system on the top of the outside roof as well as setting up the evaporator coils at ceiling.Abstract in Bahasa Indonesia : Penulisan ini merupakan suatu penelitian pada golongan sistem penghematan energi yang berupakan kondensor dengan bahan media air dengan bantuan tenaga gerak pompa atau tanpa tenaga pompa air. Pipa-pipa yang berisi air yang diletakkan diatas atap terbuka untuk mendapatkan air yang dingin melalui proses konduksi, konveksi, dan radiasi dari udara alami sepanjang malam, dimana media air yang telah dingin tersebut untuk dimanfaatkan sebagai media pendingin ruangan dengan melalukan ke pipa-pipa dalam ruangan--diatas plafon, sebagai evapurator. Selain media air akan diteliti air pendingin radiator (water coolent) apakah akan mendapatkan efek pendinginan yang melebihi media air. Juga akan diteliti cara proses mendapatkan media air dingin, yaitu proses dengan air tenang (still water) dan air bergerak (forced fluid), sistim mana yang lebih efektif dalam mendapatkan media air dingin dan percepatan mendapatkan air dingin.Kata kunci : kondensor sistim air, pendinginan pasip, temperatur ruangan.